O IMPACTO DA COORDENAÇÃO DE PROJETOS EM CANTEIRO DE OBRAS: ESTUDO DE CASO DE EMPRESAS INTERNACIONAIS ATUANDO NO BRASIL - Mognhol, Tiely; Melhado, Silvio (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The need to expand business to new markets is a growing trend. In times of crisis, this movement is advantageous for construction companies. However it is important that this movement be planned both from the strategic point of view for the company and from the managerial point of view for the projects. The objective of this research is to analyze how civil construction design coordination teams impact on the performance and results of their projects, especially regarding to international companies operating in Brazil. The research methodology was carried out in two stages: the first corresponds to a bibliographical review of relevant concepts to this study. And the second stage corresponds to a case study, being the object of this study two projects of an international company operating in the Brazilian market and two projects of a national company. As result, it was possible to verify that a company has a well organized structure for the coordination of its projects and obtained good results in the execution time of the work. The second company does not have a well-defined project coordination process, and among other executive factors, has affected in considerable delay in the work schedule.